2022
DOI: 10.1101/2022.12.12.520165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of RAS palmitoyltransferases by accessory proteins and palmitoylation

Abstract: SummaryPalmitoylation of cysteine residues at the C-terminal hypervariable regions in human HRAS and NRAS, which is necessary for the RAS signaling, is catalyzed by the acyltransferase DHHC9 in complex with its accessory protein GCP16. The molecular basis for the acyltransferase activity and the regulation of DHHC9 by GCP16 is not clear. Here we report the cryo-EM structures of the human DHHC9-GCP16 complex and its yeast counterpart — the Erf2-Erf4 complex, demonstrating that GCP16 and Erf4 are not directly in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…While this manuscript was in revision, a preprint deposited in bioRxiv reported the cryo-EM structures of human DHHC9-GCP16 and yeast Ef2-Erf4 ( Yang et al, 2022 ). Several of their findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this manuscript was in revision, a preprint deposited in bioRxiv reported the cryo-EM structures of human DHHC9-GCP16 and yeast Ef2-Erf4 ( Yang et al, 2022 ). Several of their findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the CCM motif and in particular, Cys 288, is essential for DHHC9 activity and stability. Yang et al identified palmitate on Cys288 and showed that its mutation resulted in the loss of catalytic activity ( Yang et al, 2022 ). Within the DHHC9-GCP16 structure, the palmitate attached to Cys288 in the DHHC9 α3 helix inserts adjacent to transmembrane domains 2 and 3 and the α2’ helix of GCP16, thereby promoting membrane association of the DHHC9 α3 helix and adding stability to the DHHC9-GCP16 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some cases DHHC enzymes require the chaperoning of other proteins to function as stable and active palmitoyl transferases. The best described example is the stabilization of DHHC9 by the Golgin subfamily member GCP16 13 , with a recent complex structure showing the mode of interaction 14 . The requisite interaction facilitating HRAS and NRAS palmitoylation has been established, while similar complexes involving GCP16 have been demonstrated to be required for palmitoylation by DHHC14 and DHHC18 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The best described example is the stabilization of DHHC9 by the Golgin subfamily member GCP16 13 , with a recent complex structure showing the mode of interaction 14 . The requisite interaction facilitating HRAS and NRAS palmitoylation has been established, while similar complexes involving GCP16 have been demonstrated to be required for palmitoylation by DHHC14 and DHHC18 14 . Thus, these interacting molecules might well modulate substrate specificity upon complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…The human homologs were identified as ZDHHC9, the acyltransferase of Ras, and its accessory protein GCP16, also known as GOLGA7a ( Swarthout et al, 2005 ). GCP16 has since been found to bind other acyltransferases as well, namely DHHHC5, 9, 14, and 18 ( Ko et al, 2019 ; Woodley and Collins, 2019 ; Yang et al, 2022 Preprint ). Interestingly, some ZDHHCs exhibit “polygamic” behavior, such as ZDHHC5, which can interact with both GCP16/GOLGA7a and GOLGA7b ( Ko et al, 2019 ; Woodley and Collins, 2019 ).…”
Section: Introductionmentioning
confidence: 99%